2021
DOI: 10.3390/nano11020522
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Correlation between the Amorphous Indium-Gallium-Zinc Oxide Film Quality and the Thin-Film Transistor Performance

Abstract: In this work, we performed a systematic study of the physical properties of amorphous Indium–Gallium–Zinc Oxide (a-IGZO) films prepared under various deposition pressures, O2/(Ar+O2) flow ratios, and annealing temperatures. X-ray reflectivity (XRR) and microwave photoconductivity decay (μ-PCD) measurements were conducted to evaluate the quality of a-IGZO films. The results showed that the process conditions have a substantial impact on the film densities and defect states, which in turn affect the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…When the pulse width of the laser is large enough relative to the lifetime, the peak is proportional to the lifetime. Therefore, for the evaluation of deep level traps, μ-PCD uses peak values that can be measured quickly and accurately, rather than using the lifetime value of rapid decay [ 24 ]. So, the two characteristic parameters obtained by analyzing the μ-PCD decay curve are the peak value and τ 2 , where the peak value represents the number of carriers and τ 2 is related to film uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…When the pulse width of the laser is large enough relative to the lifetime, the peak is proportional to the lifetime. Therefore, for the evaluation of deep level traps, μ-PCD uses peak values that can be measured quickly and accurately, rather than using the lifetime value of rapid decay [ 24 ]. So, the two characteristic parameters obtained by analyzing the μ-PCD decay curve are the peak value and τ 2 , where the peak value represents the number of carriers and τ 2 is related to film uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have measured the SS value by taking the inverse of the slope fitted linearly from the log-linear I ds -V gs characteristic curve [65]. The theoretical limit for the SS value of a conventional device at room temperature (300 K) is at 0.06 V/decade [66,67]. The subthreshold swing (SS) measured for the graphene-doped β-Ga 2 O 3 TFTs is ∼0.135 V/decade compared to the pristine β-Ga 2 O 3 TFTs at ∼0.189 V/decade.…”
Section: Effects Of the Graphene Doping For The β-Ga 2 O 3 Tft Devicesmentioning
confidence: 99%
“…One of the effective routines for realizing TFTs with good performance is the deposition of OS channel layers with high resistivity, followed by a postdeposition annealing treatment. Annealing is one of the most commonly used methods for optimizing active channel layers because of its effectiveness in alleviating deep traps formed by ion bombardment or unintended defects during film deposition or the synthesis process [28]. Most previous studies demonstrated that the performance of TFTs under multiple annealing conditions varies depending on the channel material and process conditions chosen [29,30].…”
Section: Introductionmentioning
confidence: 99%